Partisipasi Masyarakat pada Community Based Tourism di Desa Wisata Giyanti Kabupaten Wonosobo - Ammela Maulani; Fakhruddin Fakhruddin (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Giyanti Tourism Village in Wonosobo Regency is an example of tourism that implements full community participation in its development. This participation is expected to increase tourism productivity by utilizing the potential of culture and traditions that have long developed in the community. Giyanti tourism village presents the beauty of the performance of the Lengger Dance, Nyadran Rakanan, and the lives of rural people who are still thick with tradition. This study aims to measure the involvement of local communities in the development of community-based tourism villages as a form of community empowerment in rural areas. The method used is a qualitative approach with observation, interview, and documentation techniques, which was carried out in Giyanti Hamlet, Kadipaten Village. The research informants consisted of the head of Giyanti Hamlet, the chairman and members of the pokdarwis, the community, and members of MSMEs. The results of the study show that community participation in planning, decision-making, implementation, benefit-taking, and evaluation is in accordance with the principles of CBT and does not contradict cultural values and traditions. The high participation of the community in funding and manpower reflects the obligations that are considered part of meeting needs. However, the participation of the youth of Giyanti Hamlet in the tourism sector is still minimal. This research provides important implications for the development of policies that can encourage the involvement of the younger generation in the tourism sector, in order to achieve sustainability and improve community welfare.